Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance

Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Synthesis of 5-hydroxymethylfurfural from glucose using a tert-butoxyapatite catalyst - Kulkarni, Hemant S.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (DALTON TRANSACTIONS, 2025)
In this study, 5-hydroxymethylfurfural (5-HMF) was obtained from glucose using tert-butoxyapatite, a heterogeneous catalyst. The tert-butoxyapatite catalyst was prepared and characterized by several techniques, such as XRD, SEM, TEM, EDS, elemental mapping HR-TEM, N2-adsorption/desorption, XPS, and FT-IR. Several parameters were studied, such as temperature, catalyst loading, and glucose concentration. The tert-butoxyapatite catalyst having both acidic and basic sites gave a maximum glucose conversion of 87% with a 48% yield of HMF at 160 degrees C using 20 wt% catalyst in 12 h. Reusability studies of the catalyst are also presented.

Synthesis of glycolic acid from glyoxal by using hydrotalcite catalyst and kinetic studies - Pandya, Harmitkumar N.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (ChemCatChem, 2025)
In this work, Mg-Al hydrotalcite catalysts with different molar ratios were prepared using the co-precipitation method for the synthesis of glycolic acid (GA) from glyoxal. Various reaction parameters such as catalyst molar ratio, time, temperature, catalyst loading, and catalyst poisoning were studied and optimized for better conversion of glyoxal selectively to glycolic acid. Hydrotalcite catalyst with a 2:1 molar ratio of Mg: Al gives 98% conversion of glyoxal with 96% selectivity of glycolic acid at 100 degrees C temperature, 40% catalyst loading, and water as solvent in 8 h. Different characterization methods were used such as XRD, XPS, SEM-EDX, nitrogen adsorption desorption, and CO2-TPD for hydrotalcite catalyst. A kinetic study was also performed to observe the reaction order and activation energy required for the reaction.
Keywords: Glycolic acid; Glyoxal; hydrotalcite; kinetics